AKIBAT OvERMAcHT (KEADAAN MEMAKSA) DALAM PERJANJIAN TIMBAL BALIK - elfiani, Elfiani (Institut Agama Islam Negeri (IAIN) Bukittinggi, 2012)
Overmacht (circumtances force) is one of reasons that can be proposed by a debtor to defend themselves from breach of contract prosecution by a creditors. Overmacht is a state where the debtor can’t meet achievement to creditors, caused the event are beuond his control and his power. The key issue in overmacht is about who is at risk, if the achievement can’t be implemented properly because overmacht. In reciprocal agreement, settlement in the overmacht event based on the priciple of property. Debitors who do not carry out obligations because of overmacht can’t required to pay compensation, but he will also will not be entitled to kontraprestasi.